Ab-initio combined the Calphad approach to the phase equilibria in the ternary Ti-Mo-N system - Daclan R.A.; Mena M.G.; Vasquez M.R.; Gierlotka W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The ternary Ti-Mo-N system is an important material used as a surface coating, hardener, and wear and corrosion protection layer. Knowledge of the phase equilibria, phase transformations, and phase stabilities of this alloy is important to realizeits potential applications. In this paper, formation energies of three intermetallic compounds, Mo2N-beta, Mo2Ngamma, and MoN-delta, were determined by ab-initio calculations.Then , the Calphad approach was applied to thermodynamically model the Mo-Ti, Mo-N, and Mo-Ti-N systems. The obtained Gibbs energies were used to calculate the phase diagram and thermodynamic properties of the Ti-Mo-N system. The present model is in good agreement with experimental data reported in the literature. The results of this work can be used as a basis for future investigations of the Ti-Mo-N system, as well as a basis for practical industrial applications.